Smart graphics : third International Symposium on Smart Graphics, SG 2003, Heidelberg, Germany, July 2-4, 2003 : proceedings - Butz, A. (Springer, 2017)
This book constitutes the refereed proceedings of the 9th International Symposium on Smart Graphics, SG 2008, held in Rennes, France in August 2008.